2022
DOI: 10.1101/2022.04.21.489048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human pancreatic islet microRNAs implicated in diabetes and related traits by large-scale genetic analysis

Abstract: Genetic studies have identified ≥240 loci associated with risk of type 2 diabetes (T2D), yet most of these loci lie in non-coding regions, masking the underlying molecular mechanisms. Recent studies investigating mRNA expression in human pancreatic islets have yielded important insights into the molecular drivers of normal islet function and T2D pathophysiology. However, similar studies investigating microRNA (miRNA) expression remain limited. Here, we present data from 63 individuals, representing the largest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…We ( Figure 2C ) and others [40] found miR-214-3p associated with donor sex in human islets. The long non-coding RNA X-inactivation specific transcript (XIST, required for inducing X-chromosome inactivation in females) has been shown to interact with miR-214-3p [41].…”
Section: Discussionsupporting
confidence: 71%
“…We ( Figure 2C ) and others [40] found miR-214-3p associated with donor sex in human islets. The long non-coding RNA X-inactivation specific transcript (XIST, required for inducing X-chromosome inactivation in females) has been shown to interact with miR-214-3p [41].…”
Section: Discussionsupporting
confidence: 71%
“…We have demonstrated that different molecular phenotypes of the same genes were likely to be controlled by distinct genomic loci through distinct regulatory mechanisms, indicating the importance of integrating omics data corresponding to multi-layer biologically-important molecular phenotypes (e.g., epigenetic mark activity and microRNA expression (74)) in future studies. This is consistent with findings in humans that most of the sQTL and 3a'QTL were distinct from eQTL (75,76).…”
Section: Molqtl Mapping and The Underlying Molecular Mechanismmentioning
confidence: 99%